2009
DOI: 10.1002/lary.20107
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic tracheal rupture in children: A retrospective study

Abstract: Acute tracheal ruptures in children can be treated conservatively by bridging the rupture with a tube. Injuries to the trachea in which the mucosa is damaged or in which other complications, such as fistulae, are present must be treated surgically. The prognosis for such injuries is good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…17,18 Endotracheal intubation is associated with discomfort to the patient and may result in malposition of the tube, trauma to the airway, and hemodynamic instability. 17,1922 Endotracheal intubations have also been associated with alterations in brain function as monitored by electroencephalography. 23 …”
Section: Discussionmentioning
confidence: 99%
“…17,18 Endotracheal intubation is associated with discomfort to the patient and may result in malposition of the tube, trauma to the airway, and hemodynamic instability. 17,1922 Endotracheal intubations have also been associated with alterations in brain function as monitored by electroencephalography. 23 …”
Section: Discussionmentioning
confidence: 99%
“…1, 6 Our own experience of tracheal injuries confirms this finding. 14 Furthermore, an appropriate cuff size is required for sufficient ventilation. Despite the large number of intubations performed every day, no evidence‐based guidelines on tube selection and placement are available.…”
Section: Discussionmentioning
confidence: 99%
“…Schedlbauer et al [15] reported 18 cases of tracheal injuries in a review from 2000 to 2007 at a level I trauma center. Only four cases were found in pediatric patients, none of which were in neonates.…”
Section: Tracheal Rupture Secondary To Endotracheal Intubationmentioning
confidence: 98%